Frequency of Vitamin D Deficiency among Children with Lower Limb Angular Deformity - Asghar Ali Khan, Waseem Khan, Noor-U-Rahman, Muhammad Salar Khan, Muhammad Jawad Saleem, Muhammad Ilyas, (Pakistan Journal of Medical & Health Sciences, 2023)
Background and Aims: Vitamin D is an important biomodulator of musculoskeletal development and function. Its deficiency is a worldwide public health issue, especially among children, in whom it can cause skeletal abnormalities such as angular deformities of the lower limbs. This study aims to; (i) determine the prevalence of vitamin D deficiency in children with lower limb angular deformities; and (ii) examine the relationship between serum vitamin D concentration and the tibiofemoral joint orientation angles: the lateral distal femoral angle (LDFA) and the medial proximal tibial angle (MPTA). Material and Methods: This is a cross-sectional, observational study that was conducted at Orthopedic Department of Hayatabad Medical Complex, Peshawar, conducted between January 2023 and October 2023. The study involved 80 skeletally immature children (1-12 years) with lower limb angular deformities. Children with skeletal dysplasia, metabolic bone diseases (other than vitamin D deficiency) or a previous lower limb surgery were excluded. All participants had serum 25-hydroxyvitamin D level assessment and standardized full-length standing anteroposterior radiographs of the two lower limbs. The LDFA and MPTA were measured independently by 3 blinded observers using the digital PACS software. Statistical analysis was carried out with the use of the Statistical package for Social Sciences (SPSS) version 25 software. Results: A total of 80 children (51 boys, 29 girls) with a mean age of 4.2 years were included. The frequency of vitamin D deficiency was 63% (n=50). The mean serum vitamin D level was 28.6±19.4 ng/ml. The mean LDFA was significantly higher in the normal vitamin D group compared to the deficient group (Right LDFA: 97.9° vs. 92.7°, p=0.025; Left LDFA: 98.5° vs. 93.1°, p=0.019). A positive correlation was found between serum vitamin D levels and LDFAs (Right: ρ=0.27, p=0.03; Left: ρ=0.28, p=0.02). No significant difference or correlation was found for MPTAs. Conclusion: This study has shown a high frequency of vitamin D deficiency among children with lower limb angular deformities in our local population. The deficiency was related to changes in the LDFA rather than the MPTA, indicating that the femur may be more sensitive to the effects of vitamin D deficiency. These results highlight the need to consider screening and management of vitamin D deficiency in children with limb alignment problems. Keywords: Vitamin D deficiency, children, lower limb deformity, genu varum, genu valgum, lateral distal femoral angle, Khyber Pakhtunkhwa